1994
DOI: 10.2307/1592135
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum Infection in Chukar Partridges, Pheasants, and Peafowl

Abstract: Mycoplasma gallisepticum infection was diagnosed in a group of chukar partridges, pheasants, and peafowl based on serology and isolation techniques. The farm also had quail, chickens, and ducks. Clinical signs in growing birds consisted of foamy eyes, swollen infraorbital sinuses, respiratory distress, and death. Breeding birds experienced a severe drop in egg production. Histologically, the growing birds exhibited lymphoplasmacytic inflammation of the conjunctiva, sinus, and trachea. The most likely source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 6 publications
3
22
0
4
Order By: Relevance
“…Findings that implicate mycoplasmas in respiratory disease of game birds range from early investigations by Keymer (1961), in which a "pathogenic type" of mycoplasma was recovered in eggs, to more recent investigations of natural cases of infectious sinusitis in which M. gallisepticu m was recovered in laboratory culture medium (Poveda et al, 1986;Reece et al, 1986;Cookson & Shivaprasad, 1994). Our study appears to confirm the involvement of M. gallisepticu m in some incidents of upper respiratory disease in game birds.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Findings that implicate mycoplasmas in respiratory disease of game birds range from early investigations by Keymer (1961), in which a "pathogenic type" of mycoplasma was recovered in eggs, to more recent investigations of natural cases of infectious sinusitis in which M. gallisepticu m was recovered in laboratory culture medium (Poveda et al, 1986;Reece et al, 1986;Cookson & Shivaprasad, 1994). Our study appears to confirm the involvement of M. gallisepticu m in some incidents of upper respiratory disease in game birds.…”
Section: Discussionsupporting
confidence: 81%
“…Upper respiratory disease has been noted in pheasants and partridges in the UK and the US for many years (Gianforte et al, 1955;Wichmann, 1957;Keymer, 1958Keymer, , 1961Osborn & Pomeroy, 1958;Cookson & Shivaprasad, 1994;McMartin et al, 1996) and it has also been reported in Australia (Reece et al, 1986). The condition usually presents as conjunctivitis and sinusitis, sometimes with severe bilateral swellings of the infraorbital sinuses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O quadro clínico-patológico observado nesses dois surtos foi semelhante a outros relatos de infecção experimental e espontânea por MG em galiformes (Cookson & Shivaprasad 1994, Nunoya et al 1995, Radi et al 2000, Ley 2008, Vitula et al 2011. A lesão causada por MG ocorre especialmente nos seios nasais, traqueia e sacos aéreos, embora os pulmões também possam estar envolvidos (Fletcher et al 2008).…”
Section: Discussionunclassified
“…A ausência de monitoria constante em sistemas de produção de aves com ciclo de vida curto como os frangos de corte, bem como poedeiras, aves de criação extensivas, selvagens e ornamentais, representa uma ameaça à sanidade avícola industrial, uma vez que esses animais podem servir como reservatório de micoplasmas, mantendo-os no meio ambiente (Cookson & Shivaprasad 1994, Nunoya et al 1995, Nunoya et al 1997, Minharro et al 2001, Buim et al 2009, Gomes et al 2010, Machado et al 2012.…”
unclassified